Potential predictors for chemotherapeutic response and prognosis in epithelial ovarian, fallopian tube and primary peritoneal cancer patients treated with platinum-based chemotherapy - Dhammapoj Jeerakornpassawat; Prapaporn Suprasert (Korean Society of Obstetrics and Gynecology, 2020)
ObjectiveThis study aimed to investigate the potential predictive factors for platinum resistance and poor prognosis in epithelial ovarian, fallopian tube, and primary peritoneal cancer treated with platinum-based chemotherapy.MethodsMedical records of 306 patients with the above mentioned cancers treated with platinum-based chemotherapy between 2007 and 2017 were retrospective reviewed. Clinical data, preoperative neutrophil-to-lymphocyte ratio (NLR), platelet-to-lymphocyte ratio (PLR), platinum-free interval, and survival time were recorded. NLR, PLR, and cancer antigen 125 (CA125) levels were calculated for an optimal cutoff point using receiver operating characteristic curves. The clinicopathological variables were compared using univariate and multivariate analyses to identify independent predictive factors for platinum resistance and poor survival outcomes.ResultsThe optimal cutoff points for NLR, PLR, and CA125 were 3.38, 210, and 365 IU/L, respectively. Univariate analysis indicated that NLR >3.38, PLR >210, CA125 >365, advanced stage, suboptimal disease, serous type, and ascites were significant predictive factors for platinum resistance. However, only NLR >3.38 and advanced stage were independent predictive factors with an adjusted odds ratio of 1.880 and 3.333, respectively. Regarding factors associated with poor survival outcomes, only PLR >210 and advanced stage were independent factors, with a hazard ratio of 1.578 and 3.994, respectively.ConclusionHigh NLR and advanced stage were potential independent predictive factors for platinum resistance, whereas high PLR and advanced stage were potential independent predictive factors for poor survival outcomes.